Modified Artificial Bee Colony (ABC) Algorithm using Dynamic Technique - Samiulla Beg, Mirza; Waoo, Akhilesh A. (Asian Journal of Electrical Sciences, 2021)
The artificial Bee Colony Algorithm is a maximum optimization technique. It has been used in various research papers. In this paper, the dynamic technique has been used in Artificial Bee Colony Algorithm, before this algorithm used the greedy technology of the algorithm. But due to some deficiency in the greedy technique, it has been replaced by the dynamic technique. Here in the Artificial Bee Colony Algorithm, an attempt has been made to overcome the lack of hygiene by using the dynamic technique. The methodology is depicted in this paper. Using this methodology, you can smooth access to data in network communication, reduce data access time, and also reduce energy consumption.